Refugees' high employment expectations: Partially met - Daniel Graeber; Felicitas Schikora (DIW Weekly Report, 2020)
This report compares employment expectations among refugees in Germany in 2016 with their actual employment situation in 2018, using the IAB-BAMF-SOEP Survey of Refugees in Germany. In 2016, the majority of refugees reported that the probability they would find employment within two years was high. Employment expectations were met by 54 percent of all refugees; yet 35 percent of refugees who articulated high expectations in 2016, had no job in 2018. The findings show that both structural factors, such as a lack of childcare, and individual level characteristics, such as mental health, impacted entry into employment. Extra support for refugees seeking employment-the provision of information and advice on the German labor market, better childcare options, or support for those with mental health issues, for example-could help ensure that employment expectations are met more frequently. Further studies are needed to provide a better understanding of the different mechanisms at play here.
Keywords: D84; F22; J61; 330; refugees; expectation formation; integration; expectation error